Some Sketchy Notes on the Reaper Argument - Marko, Vladimír (Organon F, 2012)
The paper deals with the possible readings of The Reaper Argument premisses. Some conjectures related to the Stoics’ alleged proof of the argument are discussed.
Keywords: determinism; Diodorus; Megarians; non-contingency; Reaper Argument; Stoics